Impact of crop-livestock-forest integration on soil quality - Borges, Wander L. B.; Calonego, Juliano C. [UNESP]; Rosolem, Ciro A. [UNESP] (Springer, 2019)
Integrated agricultural production systems with trees, grain crops and forage species are important for land use optimization. However, they can result in non-uniform changes in physical and chemical soil properties. The objective of this work was to evaluate chemical and physical soil properties in a eucalyptus-based agroforestry system. The experiment was conducted in a Red-Yellow Argisol in Southeast Brazil. Eucalyptus (Eucalyptus grandisxE. camoldulensis) seedlings were planted in rows 12.0 m apart, and 2.0 m between plants. For 4 years the inter-row space was cropped to soybeans (Glycine max L. Merrill), Sunn hemp (Crotalaria juncea) and maize (Zea mays L.) in association with palisade grass (Urochloa brizantha). After that, the forage was grazed by beef cattle. Five years after the implementation of the experiment, chemical and physical soil analyses were performed along the profile. Non-uniform changes were observed in fertility and soil physics in the transect between the eucalyptus planting lines, both at the soil surface layers and in depth. Integrated crop/livestock production systems, where eucalyptus is intercropped with annual crops and forage grasses for grazing, results in lower soil fertility near tree lines and up to 100 cm deep over time. Next to the tree line there is an increase in soil compaction and reduced aggregate stability in the uppermost soil layer, while microporosity and soil structuring are increased in the soil deeper layers. These effects are probably due to animal trampling under the trees.
Keywords: Sustainable soil management; Eucalyptus; Cropping systems; Integrated systems